Plasmonic Nanostructures for Optically Induced Movement - Balestrieri, Sergio; Zito, Gianluigi; Coppola, Giuseppe; Iodice, Mario (Frontiers in Nanotechnology, 2022)
Optical forces generated at the nanoscale using electric field gradients have proven to be a powerful tool for trapping and moving nano-objects in a variety of application fields ranging from aerospace engineering to biology and medicine. Typically, to achieve this optical effect plasmonic resonant cavities that combine localized surface plasmon resonances and propagative surface plasmon polaritons are used. Indeed, these structures allow to engineer the distribution of the excited field hotspots, so inducing a precise movement of the nanoparticles interacting with the plasmonic field. In this paper, starting from the theoretical analysis of the surface plasmons, the potentialities of plasmonic nanostructures are reviewed, analysing the geometric conformation designed according to the application. The configurations with the most interesting performance, among those mentioned in the literature, are described in detail, examining their main characteristics and limitations. Finally, the future development and prospects of these plasmonic nanostructures are discussed.